Gastrochilus obovatifolius (Orchidaceae, Aeridinae), a new species from the Daba Mountains of Chongqing, China - Chi Xiong; Xiao-Ying Fu; Ke Tan; Ya Huang; Hong-Jing Zhang; Yi-Chen Wang; Yu-Bing Yang; Si-Rong Yi (PhytoKeys)
Gastrochilus obovatifolius, a new species discovered in the Dabashan of northeast Chongqing (China), is described and illustrated. The novelty morphologically resembles G. affinis, G. balangshanensis and G. heminii in having a glabrous and smooth epichile. but can be distinguished by the unique obovate shape of the leaves, smaller epichile, and flower color. The results of molecular phylogenetic analysis, based on nuclear ribosome internal transcribed spacer (nrITS) and four chloroplast DNA fragments (matK, psbA–trnH, psbM–trnD, and trnL–F) of 55 Gastrochilus species, support the inclusion of G. obovatifolius in G. sect. Microphylli, being most closely related to G. balangshanensis from Sichuan. The new species is a trunk epiphyte in evergreen broad-leaved forest.